LncRNA IMFNCR Promotes Intramuscular Adipocyte Differentiation by Sponging miR-128-3p and miR-27b-3p - Zhang, Meng; Li, Fang; Sun, Jun-wei; Li, Dong-hua; Li, Wen-ting; Jiang, Rui-rui; Li, Zhuan-jian; Liu, Xiao-jun; Han, Rui-li; Li, Guo-xi; Wang, Yan-bin; Tian, Ya-dong; et al. (Frontiers in Genetics, 2019)
Poultry meat quality is affected by many factors, among which intramuscular fat (IMF) is predominant. IMF content affects the tenderness, juiciness, and favor of chicken. An increasing number of studies are focusing on the functions of lncRNAs in adipocyte differentiation. However, little is known about lncRNAs associated with intramuscular adipocyte differentiation. In the present study, we focused an up-regulated lncRNA during intramuscular adipogenetic differentiation, which we named intramuscular fat-associated long noncoding RNA (IMFNCR). IMFNCR promotes intramuscular adipocyte differentiation. In-depth analyses showed that IMFNCR acts as a molecular sponge for miR-128-3p and miR-27b-3p and that PPARG is a direct target of miR-128-3p and miR-27b-3p in chicken. High-fat and high-protein diet inhibited chicken IMFNCR level in vivo. Moreover, IMFNCR level was positively correlated with PPARG mRNA level in chicken breast muscle tissues, a vital corollary to ceRNA function. Altogether, our research showed that IMFNCR acts as a ceRNA to sequester miR-128-3p and miR-27b-3p, leading to heightened PPARG expression and thus promotes intramuscular adipocytes differentiation. Taken together, our findings may contribute to a more thorough understanding of chicken IMF deposition and the improvement of poultry meat quality.